Aquatic macroinvertebrate assemblages associated with two floating macrophyte species of contrasting root systems in a tropical wetland - da Silva, Carolina Vieira; Henry, Raoul [UNESP] (Springer Nature, 2020)
Aquatic macrophytes play an important role in structuring biotic communities. A comparative study of macroinvertebrate community structures associated with Salvinia auriculata Aublet and Eichhornia crassipes (Mart.) Solms was conducted in a Brazilian wetland (São Paulo State) during two periods. Our working hypothesis is that the aquatic macrophyte with the highest root system biomass and volume (E. crassipes) will result in the highest abundance and richness of associated macroinvertebrates. There were significant differences in the taxa richness and density of macroinvertebrates between macrophytes and sampling periods. The density of macroinvertebrates was higher in S. auriculata than in E. crassipes during both sampling periods, but there was little difference in mean taxa richness. Negative correlations between the macrophyte root biomass and volume and macroinvertebrate density were found. Insecta, Crustacea and Annelida were the most numerous groups of invertebrates sampled during the study, and Diptera (Insecta) dominated in the root systems of both macrophytes. Macroinvertebrates associated with E. crassipes roots may have undergone a vertical gradient of decreased oxygen concentration in the water, as well as of the available periphyton biomass, because of the low penetration of light in the region of the root system, which resulted in a lower density of macroinvertebrates.
Keywords: Eichhornia crassipes; Freshwater ecology; Limnology; Phytofauna; Salvinia auriculata